2020
DOI: 10.1007/s00264-020-04661-3
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional femoral morphology in Hartofilakidis type C developmental dysplastic hips and the implications for total hip arthroplasty

Abstract: Purposes The aim of this study was to describe and compare the femoral morphologies of Hartofilakidis types C1 and C2 developmental dysplasia of the hip (DDH), and discuss the potential influence on subsequent total hip arthroplasty (THA). Methods We analyzed preoperative CT data from 81 patients (42 C1 and 39 C2 subtypes) who underwent THA for arthritis secondary to Hartofilakidis type C DDH. The CT data was three-dimensionally reconstructed and measured of following parameters: neck-shaft angle, femoral neck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
1
3
2
Order By: Relevance
“…Regarding the femoral neck anteversion, dysplastic femurs had a significantly larger anteversion than the normal femurs. Without the restriction of false acetabulum, the IVa femurs had a notably larger anteversion than IVb femurs, which was different from the comparable results previously [ 27 ]. Compared with the normal femur, both IVa and IVb femurs had smaller head height and IVb femurs had larger greater trochanter height, resulting in larger GT–FH height discrepancy in both DDH groups.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Regarding the femoral neck anteversion, dysplastic femurs had a significantly larger anteversion than the normal femurs. Without the restriction of false acetabulum, the IVa femurs had a notably larger anteversion than IVb femurs, which was different from the comparable results previously [ 27 ]. Compared with the normal femur, both IVa and IVb femurs had smaller head height and IVb femurs had larger greater trochanter height, resulting in larger GT–FH height discrepancy in both DDH groups.…”
Section: Discussioncontrasting
confidence: 99%
“…However, we found neck-shaft angle in the Crowe IVa group was significantly smaller than that of IVb and normal group, whereas no difference was found between IVb and normal groups. Our results were consistent with the conclusion of Liu [ 4 ] and Wang et al [ 27 ], but Du reported that the angle in IVb was larger than the contralateral normal femur [ 10 ]. The medial offset in both DDH groups was smaller than the normal group and no difference was found between DDH groups, which was consistent with results of Du [ 10 ] and Noble et al [ 15 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…To measure the neck-shaft angle, modifications of the techniques described by Wang et al [26] and Zhang et al [27] were used. Previously, the femoral head was simulated as a sphere; thus, its centers are coincident.…”
Section: Neck-shaft and Mechanical Anglementioning
confidence: 99%